ANALISIS KESESUAIAN LAHAN BUDIDAYA RUMPUT LAUT DI DESA PARUMAAN - Donny Mercys Bessie; Umbu P. L. Dawa (Partner, 2018)
One of the marine aquaculture commodities that is currently booming in East Nusa Tenggara Province and has a market prospect is seaweed. The local government of Sikka district since 2007 has declared seaweed as its main aquaculture commodity. This declaration is based on the availability of coastal land, where 90% of the territorial waters are potential for seaweed cultivation. However, this potency is oftentimes ignored. The purposes of this study are (1) to analyse the suitability area for seaweed cultivation, (2) to collect data and information about the area, water capacity, unit area, and carrying capacity of the waters. This research was conducted in the coastal area in Parumaan village, Sikka, East Nusa Tenggara Province. Analysis of area compatibility is based on the watercarrying capacities to support seaweed cultivation. The result shows that the coastal area in Parumaan was compatible for the cultivation, with a value of 270 which means that the development of seaweed is possible while still taking into account the carrying capacity of the ecosystem.